Comerţul la distanţă în Codul civil modernizat [Articol] - Calmîc, Vlada (CEP USM, 2020)
Distance trade represents the entrepreneurial activity initiated in the field of marketing the goods produced, processed or procured, as well as in the field of execution of various works and the provision of services within an organized scheme of sales or provision of remote services, administered by the entrepreneur, who uses only one or more means of distance communication for the conclusion of the contract. The institution of distance trade is not homogeneous, neither practically nor theoretically. Currently, distance trading can be regarded as a set of institutions governed by similar rules because of its specific nature.
DISTANCE TRADE IN THE MODERNIZED CIVIL CODE
Keywords: vânzare la distanță; comerț electronic